Obamacare During the Pandemic: A Historical, Economic and Sociopolitical Evaluation of the Initial Response of the US Government - Amri, Boutheina; Menazla, Nadia (Technium Social Sciences Journal, 2022)
This review of literature is an account of the US government initial response to the 2020 outbreak. The Affordable Care Act was, more so than ever, put to the test in the Covid -19 era with questions about its efficiency in healthcare delivery in this unforeseen state of emergency. This paper opted for a combination of historical and analytical reviews of literature about the American healthcare system to showcase the sociopolitical and economic implications of the COVID -19 pandemic in the earliest months of the outbreak. This study enunciates the weaknesses of federal actions in dealing with the health crisis and the dilemma of the millions of Americans who belong to minority ethnic groups who awaited equity and fast action to protect them from the severe consequences of the pandemic and the resulting recession. This investigation concluded that the ACA which was once an ambitious and very promising health care reform is struggling today to keep up with the alarming growing numbers of the uninsured or under-insured vulnerable sections of the population that it was originally designed enacted to protect. The pandemic was a very important reminder that healthcare in America is in dire need for an overarching reform. This study is a needed document that explains how healthcare in America proved once more to fail millions of Americans in a very important turning point in the recent history of healthcare delivery.